ualitas Makro Semen Ayam Kampung yang Disumplementasi L-Arginine dan L-Lysine HCl Dalam Pakan - Maria F. E. Wamur; Agustinus Agung Dethan; Charles V. Lisnahan (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2022)
This study aimed to determine the macro quality of Kampung Chicken semen supplemented with L-Arginine and L-Lysin HCl in the feed. This study used 43 domestic chickens aged 3 months, and data collection was carried out when the chickens were 5 months old. The method used in this study is an experimental method using a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications so that there are 20 experimental units. The treatments given included treatment T1 (Control Feed + L-Lysine 0,6% + L-Arginine 0,4%), T2 (Control Feed + L-Lysine 0,6% + L-Arginine 0,6%), T3 (Control Feed + L-Lysine 0,8% + L-Arginine 0,4%), and T4 (Control Feed + L-Lysine 0,8% + L-Arginine 0,6%). The data obtained were then analyzed descriptively to obtain qualitative data, and an Analysis of Variance (ANOVA) was performed to obtain quantitative data. Statistical analysis showed that the semen volume of Kampung Chicken supplemented with amino acids L-Lysine and L-Arginine in the feed had a significant effect (P<0,05) on the volume and pH of the semen. Furthermore, the results of the descriptive test of supplementation of amino acids L-Arginine and L-Lysine in the feed had no significant effect on the quality of semen odour, semen colour, and consistency/viscosity of Kampung Chicken semen. Based on the study's results, it can be concluded that adding amino acids L-Lysine and L-Arginine to feed can increase the macro quality of Kampung Chicken semen, including volume, colour, odour, consistency/thickness, and pH.